The Effect of Sugar Cane Levels and Drying Methods on Chemical and Physical Qualities of Ground Beef “Dendeng” - Jamhari Jamhari; Edi Suryanto; Sundari Sundari; Diah Ayu Laksmiwati (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study was conducted to investigate the effect of sugar cane levels and drying methods on chemical and physical quality of ground beef “dendeng”. The materials were ground beef, cane sugar, and spices consisting of salt, garlic, coriander, and galangal. The treatments were the sugar cane levels, consisting of 20, 30, and 40% (w/w of meat weight), and the drying methods, consisting of oven drying and sun drying. The oven drying was done at 50+20C for 15 hours, while sun drying was done at 40+20C for 6 hours per day for 4 days. The variables were tested on chemical quality (moisture, protein, and fat contents), and physical quality (pH and tenderness). Data were analyzed by analysis of variance of factorial pattern (3x2) of completely randomized design and continued by Duncan's new multiple ranges test. The results showed that there was an interaction between the sugar cane levels and the drying methods on the protein content and tenderness of ground beef “dendeng” (P<0.01). Sugar cane levels had significant effects on protein content and tenderness (P<0.05), but had no significant effect on moisture content, fat content, and pH value of ground beef “dendeng”. The drying methods had no significant effect on all chemical and physical variables of ground beef “dendeng”. In conclusion, there was an interaction between sugar cane levels and drying methods on the protein content and tenderness of ground beef “dendeng”. The addition of sugar cane at the levels of 40% yielded ground beef “dendeng” with the best tenderness. However, the methods of drying did not affect the chemical and physical qualities of ground beef “dendeng”.